Effects of attaching elastic bands to the waist and heels on drop jumps - Peng, H.-T.; Song, C.-Y.; Chen, Z.-R.; Lai, C.-T.; Gu, C.-Y.; Wang, L.-I (European Journal of Sport Science, 2022)
This study aimed to investigate the effects of the external load of elastic bands attached to the waist and heels to enhance the pre-activation of leg extensor muscles on drop jumps (DJs). Twelve male college athletes volunteered for this study. Eight cameras and two force platforms were used to collect data. Each subject performed DJs with elastic band loads of 0% and 20% body weight (BW) attached to the waist and heels during the airborne and landing phases from 40- and 50-cm drop heights. Repeated measures of two-way analysis of variance were performed with two loads of the elastic bands and two heights of the platform for each dependent biomechanical variable. Jump height, reactive strength index, leg stiffness, hip, knee flexion, and ankle plantarflexion angles at the initial foot contact and ankle dorsiflexion range of motion (ROM) significantly increased with 20% BW loads. The peak ground reaction force of impact, eccentric work, and hip flexion range of motion significantly decreased with 20% BW loads. The use of the elastic bands as accentuated loading during the airborne and landing phases of DJs can induce pre-activation of the joint extensors of the lower extremity to achieve stretch-shortening cycle benefits and performance and reduce the ground impact for the lower extremity.